Transcutaneous immunization with a highly active form of XCL1 as a vaccine adjuvant using a hydrophilic gel patch elicits long-term CD8+ T cell responses - Momo Kamei; Kazuhiko Matsuo; Haruka Imanishi; Yuta Hara; Ying-Shu Quen; Fumio Kamiyama; Naoki Oiso; Akira Kawada; Naoki Okada; Takashi Nakayama (Elsevier, 2020)
Memory CD8+ cytotoxic T-lymphocytes (CTLs) play a key role in protective immunity against infection and cancer. However, the induction of memory CTLs with currently available vaccines remains difficult. The chemokine receptor XCR1 is predominantly expressed on CD103+ cross-presenting dendritic cells (DCs). Recently, we have demonstrated that a high activity form of murine lymphotactin/XCL1 (mXCL1-V21C/A59C), a ligand of XCR1, can induce antigen-specific memory CTLs by increasing the accumulation of CD103+ DCs in the vaccination site and the regional lymph nodes. Here, we combined a hydrophilic gel patch as a transcutaneous delivery device and mXCL1-V21C/A59C as an adjuvant to further enhance memory CTL responses. The transcutaneous delivery of ovalbumin (OVA) and mXCL1-V21C/A59C by the hydrophilic gel patch increased CD103+ DCs in the vaccination site and the regional lymph nodes for a prolonged period of time compared with the intradermal injection of OVA and mXCL1-V21C/A59C. Furthermore, the hydrophilic gel patch containing OVA and mXCL1-V21C/A59C strongly induced OVA-specific memory CTLs and efficiently inhibited the growth of OVA-expressing tumors more than the intradermal injection of OVA and mXCL1-V21C/A59C. Collectively, this type of hydrophilic gel patch and a high activity form of XCL1 may provide a useful tool for the induction of memory CTL responses.